Writing a Literature Review in Reseach (Research Journal of Padmakanya Multiple Campus, 2023)
This paper explores what a literature review are and offers strategies into the form and construction of literature review for the scholars writing a research paper, a thesis, and, a dissertation. The “literature” of a literature review refers to any collection of materials on a topic, not necessarily the great literary texts of the world. A literature review is an essential component of research. It serves several important purposes that contribute to the overall quality and credibility of your paper, thesis, or dissertation. It discusses published information in a particular subject area, and sometimes information in a particular subject area within a certain time period.